The impact of playing method for shooting ability: A study on female basketball athletes - Roy Ardian; Matthew Szczepocki; Zaniar Dwi Prihatin Ciptadi (Journal of Applied Movement and Sport Science, 2025)
Background. The effectiveness of teaching methods in sports education has always been a key area of interest for improving athlete performance. One such method, the play method, is gaining attention for its potential to enhance physical skills while maintaining engagement and enjoyment.Objectives. This study explores the impact of the play method on improving shooting ability among female basketball athletes.Methods. This study was conducted on 37 female participants from a local basketball team, using a pretest-posttest design to assess changes in shooting performance. The tools in this study collected data directly from tests and measurements conducted on the basketball court. Students in this study practiced the basic technique (shooting at the basketball hoop) for 1 minute, which was repeated three times to achieve the best results. SPSS Version 26 was used to help analyze the data in this study.Results. The results revealed a significant improvement, with the mean pretest shooting score of 72.81 rising to 81.64 in the posttest, representing an 8.83-point increase. Statistical analysis confirmed that the data followed a normal distribution, and the play method had a statistically significant effect on shooting ability (p < 0.05). The findings highlight the value of integrating play-based techniques into sports training, particularly in youth and amateur sports settings. Conclusion. This study contributes to the existing body of research by demonstrating that the play method is not only effective in enhancing fundamental skills, such as shooting, but also provides an enjoyable and interactive approach to learning. By offering an alternative to traditional drills, the play method fosters motivation, improves skill acquisition, and can make sports education more accessible and enjoyable for athletes.